Efficacy and safety of oncolytic virus combined with chemotherapy or immune checkpoint inhibitors in solid tumor patients: A meta-analysis - Xiangxing Liu; Jiaojiao Zhang; Keqing Feng; Simin Wang; Liming Chen; Suping Niu; Qian Lu; Yi Fang (Frontiers Media S.A., 2022)
Background: In recent years, several clinical trials have focused on oncolytic virus (OVs) combined with chemotherapy or immune checkpoint inhibitors (ICIs) in solid tumor patients, which showed encouraging effects. However, few studies have concentrated on the summary on the safety and efficacy of the combined treatments. Therefore, we conducted this meta-analysis to explore the safety and curative effect of the combined therapy.Methods: We searched the PubMed, Cochrane Library, Embase, and Clinicaltrials.gov databases to comprehensively select articles on OVs combined with chemotherapy or ICIs for the solid tumor treatment. Overall survival (OS), progression-free survival (PFS), 1-year survival rate, 2-year survival rate, objective response rate (ORR), and adverse events (AEs) were the outcomes.Results: Fifteen studies with 903 patients were included in this meta-analysis. The pooled ORR was 32% [95% confidence interval (CI): 27-36%, I2 = 24.9%, p = 0.239]. Median OS and median PFS were 6.79 months (CI: 4.29-9.30, I2 = 62.9%, p = 0.044) and 3.40 months (CI: 2.59-4.22, I2 = 0.0%, p = 0.715), respectively. The 1-year survival rate was 38% (CI: 0.29-0.47, I2 = 62.9%, p = 0.044), and the 2-year survival rate was 24% (CI: 12-37%, I2 = 0.0%, p = 0.805). The most common AEs were fever (63%, CI: 57-69%, I2 = 2.3%, p = 0.402), fatigue (58%, CI: 51-65%, I2 = 49.2%, p = 0.096), chill (52%, CI: 43-60%, I2 = 0.0%, p = 0.958), and neutropenia (53%, CI: 47-60%, I2 = 0.0%, p = 0.944).Conclusion: OVs combined with ICIs showed a better efficacy than OVs combined with chemotherapy, which lends support to further clinical trials of OVs combined with ICIs. In addition, OVs combined with pembrolizumab can exert increased safety and efficacy. The toxicity of grades ≥3 should be carefully monitored and observed. However, high-quality, large-scale clinical trials should be completed to further confirm the efficacy and safety of OVs combined with ICIs.Systematic Review Registration: [https://www.crd.york.ac.uk/PROSPERO/login.php], identifier [RD42022348568].